Optimalisasi Pengelolaan Sampah Organik Rumah Tangga Menggunakan Eco-Fermentor Kompatibel di Kelurahan Mendalo Indah - Heriyanti, Heriyanti; Bemis, Restina; Sutrisno, Sutrisno; Puspitasari, Ratih Dyah; Muhaimin, Muhaimin; Adriansyah, Endi (Jurnal Pengabdian Masyarakat Pinang Masak, 2023)
Household organic waste is the largest contributor to total waste production. One effort that can be made to overcome problems caused by waste is through processing waste into eco-enzymes. Eco-enzyme is a multi-purpose liquid that can be used as a house cleaner, as well as as an effective natural fertilizer and pesticide. To make it easier to make eco-enzyme, it can be done using an eco-fermenter using simple technology. The eco-fermenter is designed using a semi-adiabatic principle with a volume of 60 liters, a kind of closed system that allows anaerobic fermentation to occur. Service activities were carried out in Mendalo Indah Village. Implementation of activities in the form of socialization and direct practice of making eco-enzyme using an eco-fermenter. The results of the activity showed that there was an increase in residents' understanding about optimizing the use of organic waste into eco-enzymes by using an eco-fermenter.